Integrated forming preparation method of continuous ceramic gradient distribution reinforced composite material component and composite material component
Through the integrated extrusion casting impregnation forming process and the continuous ceramic macro gradient stacking prepared by sintering, the problems of long preparation cycle, high cost and difficulty in realizing local orientation optimization in traditional composite material preparation methods are solved, and the performance of composite material components is achieved Gradient changes and service performance improvements.
Patent Information
- Application Number
- CN202411521320.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional composite material preparation methods have problems such as long preparation cycle, high cost, difficulty in achieving local orientation optimization, and easy process defects, especially during the operation of the load-bearing member.
The integrated extrusion casting impregnation forming process is adopted to prepare continuous ceramic macro gradient stacks of different densities through sintering, and combined with the extrusion casting impregnation connection of the aluminum alloy matrix, to achieve directional editing optimization and local enhancement.
The gradient changes in wear resistance, toughness and strength properties of composite components are achieved, which shortens the preparation cycle, reduces production costs, and improves the service performance of the material.
Smart Images

Figure CN119387561A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material processing engineering, and in particular to a preparation method for integrated forming of a continuous ceramic gradient distribution reinforced composite material component and a composite material component. Background Art
[0002] At present, metal matrix composites are the most widely used and most common composite materials. Their main form is to use metal or alloy as the matrix and continuous or discontinuous reinforcements through various preparation processes. On the one hand, traditional uniform composite materials are prone to segregation, and on the other hand, the particle reinforcement volume fraction has an upper limit, which is difficult to meet the actual working conditions. By mixing continuous ceramics with particle ceramics and continuous ceramics, the reinforcement phase volume fraction can be above 50%, which greatly improves the hardness and wear resistance of the composite material; composite materials reinforced by particle dispersion have the problem of uneven particle distribution. Continuous ceramic reinforced composites solve the problem of uneven distribution of reinforcement phase and limited performance of composite materials due to their unique three-dimensional network structure. At the same time, considering the special use requirements of load-bearing components during service, it is necessary to optimize the overall or local performance of the components. Conventional composite material reinforcement is generally particle dispersion reinforcement, and the preparation method adopted is powder metallurgy. This preparation method has a long production cycle and high cost, and it is difficult to achieve local directional optimization. In addition, the traditional gravity casting integrated forming process is prone to defects such as shrinkage cavities and shrinkage, which have a great impact on the overall strength of the component, and the wetting effect between the components is poor, making it difficult to achieve combination with the reinforcement phase. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a preparation method for integrated forming of a continuous ceramic gradient distribution reinforced composite material component, which has a short extrusion casting forming process and good pressure infiltration effect. Through the extrusion casting integrated forming process, a composite material with gradient changes in properties such as wear resistance, toughness, and strength is prepared. At the same time, the continuous ceramic macro-gradient stacks of different densities are prepared by sintering, and then connected by extrusion casting infiltration and integration forming of an aluminum alloy matrix to obtain a directional editing optimization and locally enhanced near-net-shaped composite component. The process characteristics of extrusion casting high-pressure solidification crystallization, high-temperature plastic deformation, static liquid forced shrinkage and pressure infiltration are fast, wettability is good, and defects are few, so as to give full play to the multi-factor strengthening coupling effect and improve the service performance of composite material components.
[0004] The present invention provides a preparation method for integrated forming of a continuous ceramic gradient distribution reinforced composite material component, which comprises the following steps:
[0005] S1. Preparing a continuous porous ceramic preform: According to the service requirements of the wear resistance and thermal conductivity of the composite material component, the continuous porous ceramic preforms with the first porosity, the second porosity and the third porosity are prepared respectively by using an organic foam template method;
[0006] S11, designing and preparing a continuous porous ceramic preform having a first porosity;
[0007] S12, designing and preparing a continuous porous ceramic preform having a second porosity;
[0008] S13, designing and preparing a continuous porous ceramic preform having a third porosity;
[0009] S2. Design, process and assemble the squeeze casting and infiltration integrated forming mold: design and process the squeeze casting and infiltration integrated forming mold and install the heating and cooling system according to the shape structure and service performance requirements of the component;
[0010] S3. Preparation of continuous ceramic gradient distribution reinforced composite components:
[0011] S31, refining the metal matrix: placing the metal matrix rod in a smelting furnace for smelting, adding a refining agent to refine the melt when the melt temperature reaches 750-800°C, stirring the refining agent and the molten metal matrix evenly, refining for 5-10 minutes, cooling at room temperature to a casting temperature of 650-680°C, and obtaining a refined metal matrix;
[0012] S32, preheating the mold and the continuous porous ceramic preform: regulating the mold heating system to preheat the mold, the mold preheating temperature is controlled at 300-350° C., and the preheating temperature of the continuous porous ceramic preform is controlled at 400-500° C.;
[0013] S33, squeeze casting and infiltration integrated forming: when the refined metal matrix prepared in step S31,
[0014] When the mold temperature and the preheating temperature of the ceramic preform reach the predetermined values, the hydraulic press is started, and the continuous ceramic preforms with different porosities are stacked in order from large to small and placed in the mold cavity, and the refined metal matrix described in step S31 is poured into the preheated mold, and the mold is closed and pressurized. The pressurizing load is 35-50MPa, and the mold is opened after holding the pressure for 40-60s. During the pressurization process, the refined metal matrix penetrates the continuous ceramic preforms with different porosities from top to bottom, and the continuous ceramic preforms with different porosities are combined with each other. After cooling for 2-5 minutes, the mold is demolded to obtain a continuous porous ceramic gradient distribution reinforced metal matrix composite material component.
[0015] Preferably, step S11 includes the following sub-steps:
[0016] S111, preparing ceramic slurry by mixing ceramic powder, solvent and additive according to a first set ratio;
[0017] S112, modifying the organic foam having the first porosity to prepare an organic foam template;
[0018] S113, immersing the organic foam template prepared in step S112 into the ceramic slurry prepared in step S111 for infiltration and slurrying, removing excess slurry on the surface of the organic template after the infiltration and slurrying is completed, and placing the organic template in a drying oven at a temperature of 80-100° C. for drying for 24-30 hours to obtain a continuous porous ceramic preform with a first porosity;
[0019] S114, placing the porous ceramic preform prepared in step S113 into a high-temperature sintering furnace for heating according to a set temperature rise program to obtain a continuous porous ceramic preform with a first porosity.
[0020] Preferably, the specific preparation method for preparing a continuous porous ceramic preform having a second porosity designed in step S12 and the specific preparation method for preparing a continuous porous ceramic preform having a third porosity designed in step S13 are different from the specific preparation method for preparing a continuous porous ceramic preform having a first porosity designed in step S11 in that the porosities of the organic foam templates selected in step S12 and step S13 are the second porosity and the third porosity, respectively.
[0021] Preferably, when the mold temperature rises to 100-200°C in step S32, graphite is sprayed on the inner surface of the mold, and the sprayed graphite serves as a release agent to assist in demolding the composite component; before preheating the continuous porous ceramic preform in step S32, ultrasonic cleaning is required for 5-10 minutes, and the preheating temperatures of the continuous porous ceramic preform having the first porosity, the continuous porous ceramic preform having the second porosity, and the continuous porous ceramic preform having the third porosity are kept consistent.
[0022] Preferably, the temperature rising program in step S113 is to first rise to 700-800°C, keep warm for 1-2 hours, then quickly rise to 1200-1400°C and keep warm for 2-3 hours, and then sinter and solidify when the temperature rises to 1200-1300°C.
[0023] Preferably, the refining agent includes a variety of inorganic salts, which appear as white powdery particles, the ceramic powder is selected from Al2O3, ZrO2, SiC or TiB2, the additives include alkali metal oxide sintering aids, high-temperature binders, low-temperature binders, dispersants, defoamers, rheological agents and surfactants, and the solvent is distilled water.
[0024] Preferably, the organic foam is polyester foam or polyurethane foam, and the specific steps of the modification of the organic foam are: cutting the organic foam according to the mold size, soaking the cut organic foam in a NaOH solution for 50-70 minutes, and then soaking the organic foam in a 1-2wt.% hydroxymethyl cellulose solution for 8-9 hours to obtain an organic foam template.
[0025] Preferably, in the process of preparing ceramic slurry in step S111, the first set proportions of ceramic powder, solvent and additives are distributed as follows: the refining agent is controlled at 0.3%-0.6% of the weight of the metal matrix, the mass of the ceramic powder accounts for 65wt.%-75wt.%, the mass of the sintering aid accounts for 10-14wt.%, the mass of the high-temperature binder accounts for 4-6wt.%, the mass of the low-temperature binder accounts for 13-17wt.%, the mass of the dispersant accounts for 0.1-0.3wt.%, the mass of the rheological agent and surfactant accounts for 0.1-0.3wt.%, and the mass of the defoaming agent accounts for 0.4-0.6wt.%.
[0026] The second aspect of the present invention provides a composite material component prepared according to the above-mentioned preparation method for integrated forming of continuous ceramic gradient distribution reinforced composite materials. The composite material component uses an aluminum alloy as a matrix and a continuous porous ceramic with a density gradient change along a preset direction as a reinforcing phase. It is prepared by an extrusion casting infiltration integrated forming method to have gradient-changing wear resistance, toughness and strength properties.
[0027] Compared with the prior art, the present invention has the following advantages:
[0028] 1. The continuous ceramic gradient distribution reinforced composite material component of the present invention adopts an extrusion casting infiltration integrated forming process, which effectively shortens the preparation cycle and production cost. The extrusion casting infiltration integrated forming process not only utilizes the process advantages of extrusion casting high-pressure solidification crystallization, high-temperature plastic deformation, and hydrostatic forced shrinkage, but also uses the process characteristics of pressure infiltration with fast speed, good wettability and few defects to achieve the infiltration connection and solidification forming of the alloy matrix in the continuous porous ceramic, exerts the effect of multi-factor strengthening coupling, and improves the service performance of the composite material component.
[0029] 2. The continuous ceramic gradient distribution reinforced composite material component of the present invention changes the wettability of the continuous ceramic by changing its porosity, and can be applied to the preparation of composite material components of various metal matrices. The continuous ceramic gradient distribution reinforced composite material is reinforced by mixing continuous ceramic with granular ceramic and continuous ceramic to achieve a reinforced phase volume fraction of more than 50%, thereby improving the hardness and wear resistance of the composite material. In addition, due to the gradient distribution of porosity, the wear resistance, toughness, strength and other properties of the composite material itself can achieve gradient changes, thereby enhancing local wear resistance and optimizing editing.
[0030] 3. The continuous ceramic gradient distribution reinforced composite material component of the present invention presents a multi-gradient configuration with macroscopic non-uniform and microscopic uniform distribution. This configuration design is conducive to overcoming the inverted relationship between strength and toughness of traditional composite materials. In addition, the continuous non-uniform configuration of the alloy matrix phase and the porous ceramic reinforcement phase in the composite material component of the present invention not only has the advantages of high specific strength and good toughness of the alloy matrix, but also has the material properties of light weight, high hardness and high wear resistance of continuous porous ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A three-dimensional modeling diagram of a continuous ceramic gradient distribution reinforced composite material component of the present invention;
[0032] Figure 2 This is a physical picture of the ceramic skeleton of the continuous ceramic gradient distribution reinforced composite material component of the present invention;
[0033] Figure 3 The present invention is a flow chart for preparing a continuous ceramic gradient distribution reinforced composite material component;
[0034] Figure 4 It is a front view of a mold for the integrated forming process of preparing a continuous ceramic gradient distribution reinforced composite material component of the present invention;
[0035] Figure 5a-Figure 5b It is a front view and a top view of a lower sample in a friction and wear test of a continuous ceramic gradient distribution reinforced composite material component of the present invention;
[0036] Figure 5c-5d It is a front view and a top view of the upper sample in the friction and wear test of the continuous ceramic gradient distribution reinforced composite material component of the present invention;
[0037] Figure 6a The relationship between the change of friction coefficient of the two assemblies with the increase of time in the friction and wear test of the assembly of the continuous ceramic gradient distribution reinforced composite material component of the present invention as the lower specimen and GCr15 as the upper specimen and the assembly of cast iron as the lower specimen and GCr15 as the upper specimen;
[0038] Figure 6b The average friction coefficient of the two assemblies in the friction and wear test of the assembly of the continuous ceramic gradient distribution reinforced composite material component of the present invention as the lower specimen and GCr15 as the upper specimen and the assembly of the cast iron as the lower specimen and GCr15 as the upper specimen;
[0039] Figure 6cThe relationship between the temperature of the two assemblies as time increases in a friction and wear test of a combination of a continuous ceramic gradient distribution reinforced composite material component of the present invention as a lower specimen and GCr15 as an upper specimen and a combination of a cast iron as a lower specimen and GCr15 as an upper specimen;
[0040] Figure 7a-Figure 7b The microscopic morphology image of the wear part of the lower end surface after the friction and wear test of the combination of the continuous ceramic gradient distribution reinforced composite material component of the present invention as the lower specimen and GCr15 as the upper specimen;
[0041] Figure 7c-7d This is the microscopic morphology image of the wear area on the lower end surface after the friction and wear test of the combination of cast iron as the lower specimen and GCr15 as the upper specimen.
[0042] Main reference numerals:
[0043] Upper die assembly 1, upper die sleeve 11, upper die body 12, upper die plate 13, disc spring 14, guide sleeve 15, upper punch 16, lower die assembly 2, lower die sleeve 21, lower die body 22, ejector pin 23, ejector pin tray 24, lower die plate 25, lower protrusion 26. DETAILED DESCRIPTION
[0044] In order to fully describe the technical content, structural features, objectives and effects of the present invention, the following will be described in detail with reference to the accompanying drawings.
[0045] like Figure 1-Figure 2 As shown, a continuous ceramic gradient distribution reinforced composite material component provided by the present invention has a porosity distribution that increases from bottom to top, wherein the continuous ceramic gradient distribution reinforced composite material component uses a metal material as a matrix phase and a continuous ceramic preform as a reinforcement phase, and is prepared by a liquid die forging integrated forming process; the metal material as the matrix phase needs to have good fluidity to facilitate the metal matrix to fully complete the infiltration process of the ceramic reinforcement phase during the forming process, and the metal matrix in the preparation process can usually choose Al-Mg-Si series, Al-Mg-Si-Cu series, Al-Zn-Mg-Cu series aluminum alloy or Mg-Al-Zn series magnesium alloy, and the continuous ceramic preform as the reinforcement phase is prepared by an organic foam impregnation method, and the combination of a slurry hanging process and a sintering process can make the prepared continuous ceramic preform more uniform and have a low preparation cost, and the metal matrix and the ceramic reinforcement phase adopt a liquid die forging integrated forming process, which ensures that the continuous ceramic gradient distribution reinforced composite material component of the present invention has a small plastic deformation and a high bonding of the components.
[0046] like Figure 3 As shown, the preparation flow chart of the preparation method of the continuous ceramic gradient distribution reinforced composite material component provided by the present invention, the specific steps are as follows:
[0047] S1. Preparation of continuous porous ceramic preforms: According to the service requirements of component wear resistance and thermal conductivity, the component configuration is directional edited and optimized, and a variety of continuous porous ceramic preforms with different densities are prepared using an organic foam template method.
[0048] S11. Designing and preparing a continuous porous ceramic preform with a first porosity.
[0049] S111, preparing ceramic powder, solvent and additive into ceramic slurry according to a first set ratio.
[0050] Among them, the ceramic powder can be selected from Al2O3, ZrO2, SiC or TiB2, etc., and the additives include alkali metal oxide sintering aids, etc.
[0051] Specifically, in the process of preparing ceramic slurry, silica powder or kaolin is used as a sintering aid, bentonite or talc is used as a high-temperature binder, industrial silica sol is used as a low-temperature binder, polyacrylamide aqueous solution is used as a dispersant, carboxymethyl cellulose aqueous solution is used as a rheological agent and surfactant, n-octanol is used as a defoaming agent, and distilled water is used as a slurry solvent.
[0052] Furthermore, the mass of ceramic powder accounts for 65wt.%-75wt.%, the mass of sintering aid accounts for 10-14wt.%, the mass of high-temperature binder accounts for 4-6wt.%, the mass of low-temperature binder accounts for 13-17wt.%, the mass of dispersant accounts for 0.1-0.3wt.%, the mass of rheological agent and surfactant accounts for 0.1-0.3wt.%, the mass of defoamer accounts for 0.4-0.6wt.%, and the rest is distilled water.
[0053] S112, modifying the organic foam of the first porosity to prepare an organic foam template.
[0054] Among them, the organic foam can be selected from polyester foam or polyurethane foam. The modification treatment of the organic foam can improve the slurry hanging effect. The specific steps are: cutting the organic foam according to the mold size, soaking the cut organic foam in NaOH solution for 50-70 minutes, and then soaking the polyurethane foam in 1-2wt.% hydroxymethyl cellulose solution for 8-9 hours to obtain an organic foam template.
[0055] S113, immersing the organic foam template prepared in step S112 into the ceramic slurry prepared in step S111 for multiple times of wetting and slurry coating, removing excess slurry after the coating is completed, and placing the template in a drying oven at 80-100°C for drying for 24-30 hours to obtain a porous ceramic preform.
[0056] S114, placing the porous ceramic preform prepared in step S113 into a high-temperature sintering furnace for heating according to a set temperature rise program to obtain a continuous porous ceramic preform with a first porosity.
[0057] The temperature rise program is set to first rise to 700-500°C, keep warm for 1-2 hours, then quickly rise to 1200-1400°C and keep warm for 2-3 hours, and sinter and solidify when the temperature rises to the range of 1200-1300°C.
[0058] Furthermore, when the temperature reaches 700° C., the organic foam in the porous ceramic preform undergoes a fat expulsion reaction, that is, the organic foam decomposes at high temperature, and the various decomposed substances are gradually ablated under high temperature conditions.
[0059] S12, preparing a continuous porous ceramic preform with a second porosity. The specific preparation steps are the same as the preparation steps of S11, except that the porosity of the organic foam template used is the second porosity.
[0060] S13, preparing a continuous porous ceramic preform with a third porosity. The specific preparation steps are the same as the preparation steps of S11, except that the porosity of the organic foam template used is the third porosity.
[0061] S2. Design, processing and assembly of squeeze casting and infiltration integrated forming molds: Design squeeze casting and infiltration integrated forming molds according to the shape structure and service performance requirements of the components, design the heating and cooling systems, and install the molds on the hydraulic press.
[0062] S3. Preparation of continuous porous ceramic gradient distribution reinforced composite components:
[0063] S31. Melting aluminum alloy matrix: placing aluminum alloy matrix rods in a melting furnace for melting, adding a refining agent when the melt temperature reaches 750-800°C, stirring the melt evenly to refine it, and after refining for 5-10 minutes, cooling it to the casting temperature of 650-680°C at room temperature.
[0064] Furthermore, the dosage of the refining agent is generally controlled at 0.3%-0.6% of the weight of the aluminum alloy. The refining agent includes a mixture of various inorganic salts and has the appearance of white powder particles. The refining mechanism of the refining agent is as follows: when the refining agent is placed in the molten metal liquid and gently stirred with a stirring rod, the refining agent forms a large number of small bubbles in the molten metal liquid through a series of physical changes and chemical reactions. These small bubbles can fully contact with the molten metal liquid and separate hydrogen and other harmful gases in the molten metal liquid; in addition, some substances contained in the refining agent have strong adsorption capacity. These components with adsorption capacity adsorb and dissolve oxides and suspended matter in the metal melt, and attach the adsorbed and dissolved products to the bubbles. As the bubbles rise, they gather on the surface of the molten metal liquid, thereby achieving the effect of degassing and slag removal.
[0065] S32. Preheating of the mold and the continuous porous ceramic preform: Regulate the mold heating system, heat slowly, preheat the mold, the preheating temperature is 300°C, when the mold temperature reaches 100°C-200°C, spray graphite on the mold surface; an appropriate amount of graphite can be used as a release agent, which is beneficial for the subsequent demolding of the product. After ultrasonically cleaning the continuous porous ceramic preform for 5-10 minutes, put it into a heating furnace for preheating and insulation at 400°C-500°C.
[0066] S33, extrusion casting and infiltration integrated forming: start the hydraulic press when the refined metal matrix melt temperature cools to 650-680℃ and the mold temperature and the preheating temperature of the ceramic preform reach the preset values; open the mold cavity, first stack the continuous ceramic preforms of different densities in order from large to small and put them into the mold, slowly pour a certain amount of liquid aluminum alloy matrix into the mold, quickly close the mold and pressurize, load 35-50MPa, maintain the pressure for 40s and open the mold, during the pressurization process, the liquid aluminum alloy matrix slowly penetrates the continuous ceramic preforms of different densities from top to bottom, when the liquid aluminum alloy matrix completely covers the continuous ceramic preforms of different densities, the continuous ceramic preforms of different densities are tightly combined, thereby preparing a continuous porous ceramic gradient distribution reinforced composite material component; after the product cools for 2-5min, demold the product.
[0067] The continuous ceramic gradient distribution reinforced composite material component of the present invention is further described below in conjunction with the embodiments:
[0068] Embodiment: A friction and wear experiment is conducted by preparing a combination of a continuous ceramic gradient distribution reinforced composite material component as a lower specimen and GCr15 as an upper specimen.
[0069] S1. Preparation of continuous porous ceramic preforms: According to the service requirements of component wear resistance and thermal conductivity, the component configuration is directional edited and optimized, and a variety of continuous porous ceramic preforms with different densities are prepared using an organic foam template method.
[0070] S11. According to the service requirements, a continuous porous ceramic preform with a porosity of 43% is designed and prepared.
[0071] S111. Ceramic powder, solvent and additives are prepared into ceramic slurry according to the above-set proportions, wherein the additives are alkali metal oxide sintering aids and other additives.
[0072] S112. Select a polyurethane foam template with a porosity of 43% and machine it into a certain shape and size.
[0073] S113, immersing the organic foam template machined in step S112 into the ceramic slurry prepared in S111 to wet and coat the slurry, removing excess slurry and placing in a 100° C. drying oven for 24 hours.
[0074] S114, placing the porous ceramic preform dried in step S113 into a high-temperature sintering furnace for degreasing and sintering, the process includes first heating to 700°C and keeping it for one hour to degreasing, then directly heating to 1200°C and keeping it for 2 hours to sinter, to obtain a continuous porous ceramic preform with a porosity of 43%.
[0075] S12. According to the service requirements, a continuous porous ceramic preform with a porosity of 55% is designed and prepared. The specific preparation steps are the same as step S11, except that the porosity of the polyurethane foam template used is 55%.
[0076] S13. According to the application requirements, a continuous porous ceramic preform with a porosity of 62% is designed and prepared. The specific preparation steps are the same as steps S11 and S12, except that the porosity of the organic foam template used is 62%.
[0077] S2. Design, processing and assembly of squeeze casting and infiltration integrated forming molds: Design squeeze casting and infiltration integrated forming molds according to the shape structure and service performance requirements of the components, design the heating and cooling systems, and install the molds on the hydraulic press.
[0078] S3. Preparation of continuous porous ceramic gradient distribution reinforced composite components:
[0079] S31. Melting of aluminum alloy matrix: Place aluminum alloy matrix rods in a melting furnace for melting. When the melt temperature reaches 750°C, add a refining agent and stir the melt evenly to refine it. After refining for 5 minutes, cool it to the casting temperature of 650°C at room temperature.
[0080] S32, preheating the mold and the continuous porous ceramic preform: regulating the mold heating system, slowly heating, preheating the mold, the preheating temperature is 300 ° C, when the mold temperature reaches 100 ° C, spraying graphite treatment on the mold surface; ultrasonically cleaning the continuous porous ceramic preform for 5 minutes, and then putting it into a heating furnace for preheating at 400 ° C; wherein the mold is as follows Figure 4 As shown, the mold includes an upper mold assembly 1 and a lower mold 2. The upper mold assembly is a convex mold, including an upper mold sleeve 11, an upper mold body 12, an upper mold plate 13, a disc spring 14, a guide sleeve 15, and an upper convex mold 16. The lower mold assembly is a concave mold, including a lower mold sleeve 21, a lower mold body 22, a push rod 23, a push rod tray 24, a lower mold plate 25, and a lower protrusion 26. Among them, the push rod tray 24 is assembled on the press beam and the workbench. The upper mold body 12 and the upper mold sleeve 11 are connected by bolts to form a forming mold convex mold, and the lower mold sleeve 21, the lower mold body 22, the push rod tray 24, and the lower mold sleeve 21 constitute a mold concave mold. During liquid die forging, the cavity formed by the concave mold and the convex mold is used to realize the forming of the metal liquid under the pressure of the mold. The mold is designed with a local loading and shrinkage compensation device, which can pressurize and compensate the workpiece during the forming process to improve the organizational properties of the workpiece and the bonding strength between the continuous ceramic and the matrix.
[0081] S33, extrusion casting and infiltration integrated forming: start the hydraulic press when the refined metal matrix melt temperature cools to 650°C and the mold temperature and the ceramic preform preheating temperature reach the preset values; open the mold cavity, first stack the continuous ceramic preforms of different densities from large to small and put them into the mold, slowly pour a certain amount of liquid aluminum alloy matrix into the mold, quickly close the mold and pressurize, load 35-50MPa, maintain the pressure for 40s and open the mold, so as to prepare a continuous porous ceramic gradient distribution reinforced aluminum-based composite material component; demold and take out the part after the part cools for 2 minutes.
[0082] Comparative example: A friction and wear test was conducted by using a combination of cast iron as a lower specimen and GCr15 as an upper specimen.
[0083] Figure 6a The relationship between the change of the friction coefficient of the material surface and time during the test process. The maximum friction coefficient of the composite component-GCr15 in the wear test is 0.387, and the maximum friction coefficient of HT250-GCr15 in the wear test is 0.404; Figure 6b is the average friction coefficient of the two experimental groups. The average friction coefficient measured in the embodiment is 0.314, and the average friction coefficient measured in the comparative example is 0.327. The wear rate of the composite material is roughly in the range of 7.0-7.8 mg / (km·N), and the wear rate of HT250 is roughly in the range of 13.0-14.0 mg / km·N. Figure 6cThe middle shows the temperature changes of the two groups of tests during the friction and wear test. As the test time progresses, the temperature tends to rise, but the temperature of the composite material is generally lower than HT250. The reason is that compared with HT250, the composite material component of the present invention has higher strength and hardness of the ceramic phase, while the aluminum alloy is softer. During the wear process, the heat is dissipated with the wear debris, and the ceramic phase is exposed after the aluminum alloy material is worn, which is not easy to wear, so that a small gap is generated on the contact surface, and the heat is easier to dissipate, which reduces the thermal weakening phenomenon of the material and reduces the generation of thermal cracks.
[0084] Figure 7 is a microscopic image of the wear area on the lower end surface. Figure 7a , Figure 7b For the microscopic morphology of the composite material after wear, the aluminum alloy matrix part wears earlier than the Al2O3 ceramic. The aluminum matrix material is worn and consumed quickly, causing the ceramic phase to appear. Track-like scratches can be seen on the aluminum alloy matrix part, and the scratches begin to fade and disappear when they extend to the position of the ceramic phase. This is because the ceramic phase has high strength and hardness, and has a strong ability to resist plastic deformation when subjected to GCr15 material wear, and cracks are not easy to initiate and expand. When the ceramic phase is exposed, most of the load pressure and scraping groove tangential force are borne by the Al2O3 ceramic. The Al2O3 ceramic plays a good protective role on the aluminum alloy matrix, and there is no direct load acting on the aluminum alloy matrix, thereby changing the wear mechanism of the matrix phase and reducing the wear and consumption of the matrix phase.
[0085] Figure 7c , Figure 7d This is the microstructure of HT250 after wear. Figure 7c It can be seen that there are large pieces of wear debris distributed along the friction direction on the scratches, which are the main characteristics of adhesive wear. When the friction surfaces of the HT250 material and the GCr15 material slide relative to each other, the molecular bonding on the interface causes adhesive coupling on the contact surface. The friction force at the adhesion node increases during the movement, and the shear stress is large, which will cause the relatively soft HT250 material to shear and break at the adhesion point, causing scratches on the surface of the HT250 material. Figure 7c and Figure 7d In addition to the long scratches and scrapes, there are also a large number of uneven peeling pits, which are the main characteristics of peeling wear.
[0086] In summary, after the ceramic phase is exposed during the wear process of Al2O3 continuous ceramic reinforced ZL2A50 aluminum alloy composite material, the bearing capacity is stronger than that of HT250, and Al2O3 continuous ceramic is not prone to cracks and large-scale spalling.
[0087] The embodiments described above are only descriptions of the preferred implementation modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming, characterized in that: It includes the following steps: S1. Preparing a continuous porous ceramic preform: according to the service requirements of the wear resistance and thermal conductivity of the composite material component, using an organic foam template method to prepare continuous porous ceramic preforms with a first porosity, a second porosity and a third porosity; S11, designing and preparing a continuous porous ceramic preform having a first porosity; S12, designing and preparing a continuous porous ceramic preform having a second porosity; S13, designing and preparing a continuous porous ceramic preform having a third porosity; S2. Design, process and assemble the squeeze casting and infiltration integrated forming mold: design and process the squeeze casting and infiltration integrated forming mold and install the heating and cooling system according to the shape structure and service performance requirements of the component; S3. Preparation of continuous ceramic gradient distribution reinforced composite components: S31, refining the metal matrix: placing the metal matrix rod in a smelting furnace for smelting, adding a refining agent to refine the melt when the melt temperature reaches 750-800°C, stirring the refining agent and the molten metal matrix evenly, refining for 5-10 minutes, cooling at room temperature to a casting temperature of 650-680°C, and obtaining a refined metal matrix; S32, preheating the mold and the continuous porous ceramic preform: regulating the mold heating system to preheat the mold, the mold preheating temperature is controlled at 300-350° C., and the preheating temperature of the continuous porous ceramic preform is controlled at 400-500° C.; S33, extrusion casting infiltration integrated forming: when the refined metal matrix prepared in step S31, the mold temperature and the preheating temperature of the ceramic preform reach the predetermined values, start the hydraulic press, stack the continuous ceramic preforms with different porosities in order from large to small and place them into the mold cavity, pour the refined metal matrix described in step S31 into the preheated mold, close the mold and pressurize with a pressurizing load of 35-50MPa, maintain the pressure for 40-60s and open the mold, during the pressurization process, the refined metal matrix penetrates the continuous ceramic preforms with different porosities from top to bottom, the continuous ceramic preforms with different porosities are combined with each other, and demolding is performed after cooling for 2-5 minutes to obtain a continuous porous ceramic gradient distribution reinforced metal matrix composite material component.
2. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1, characterized in that: Step S11 includes the following sub-steps: S111, preparing ceramic slurry by mixing ceramic powder, solvent and additive according to a first set ratio; S112, modifying the organic foam having the first porosity to prepare an organic foam template; S113, immersing the organic foam template prepared in step S112 into the ceramic slurry prepared in step S111 for infiltration and slurrying, removing excess slurry on the surface of the organic template after the infiltration and slurrying is completed, and placing the organic template in a drying oven at a temperature of 80-100° C. for drying for 24-30 hours to obtain a continuous porous ceramic preform with a first porosity; S114, placing the porous ceramic preform prepared in step S113 into a high-temperature sintering furnace for heating according to a set temperature rise program to obtain a continuous porous ceramic preform with a first porosity.
3. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1, characterized in that: The specific preparation method for preparing a continuous porous ceramic preform with a second porosity designed in step S12 and the specific preparation method for preparing a continuous porous ceramic preform with a third porosity designed in step S13 are different from the specific preparation method for preparing a continuous porous ceramic preform with a first porosity designed in step S11 in that the porosities of the organic foam templates selected in step S12 and step S13 are the second porosity and the third porosity, respectively.
4. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1, characterized in that: In step S32, when the mold temperature rises to 100-200°C, graphite is sprayed on the inner surface of the mold, and the sprayed graphite serves as a release agent to assist in demolding the composite component; in step S32, the continuous porous ceramic preform needs to be ultrasonically cleaned for 5-10 minutes before preheating, and the preheating temperatures of the continuous porous ceramic preform with the first porosity, the continuous porous ceramic preform with the second porosity, and the continuous porous ceramic preform with the third porosity are kept consistent.
5. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1, characterized in that: The temperature rising program in step S113 is to first raise the temperature to 700-800°C, keep it warm for 1-2 hours, then quickly raise the temperature to 1200-1400°C and keep it warm for 2-3 hours, and when the temperature rises to 1200-1300°C, sinter and solidify.
6. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1, characterized in that: The refining agent includes a variety of inorganic salts and has the appearance of white powder particles. The ceramic powder is selected from Al2O3, ZrO2, SiC or TiB2. The additives include alkali metal oxide sintering aids, high-temperature binders, low-temperature binders, dispersants, defoamers, rheological agents and surfactants. The solvent is distilled water.
7. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1, characterized in that: The organic foam is polyester foam or polyurethane foam. The specific steps of the modification of the organic foam are: cutting the organic foam according to the mold size, soaking the cut organic foam in NaOH solution for 50-70 minutes, and then soaking the organic foam in 1-2wt.% hydroxymethyl cellulose solution for 8-9 hours to obtain an organic foam template.
8. The method for preparing a continuous ceramic gradient distribution reinforced composite material component by integrated forming according to claim 1 or 2, characterized in that: In the process of preparing ceramic slurry in step S111, the first set proportion of ceramic powder, solvent and additive is distributed as follows: the refining agent is controlled at 0.3%-0.6% of the weight of the metal matrix, the mass of the ceramic powder accounts for 65wt.%-75wt.%, the mass of the sintering aid accounts for 10-14wt.%, the mass of the high-temperature binder accounts for 4-6wt.%, the mass of the low-temperature binder accounts for 13-17wt.%, the mass of the dispersant accounts for 0.1-0.3wt.%, the mass of the rheological agent and surfactant accounts for 0.1-0.3wt.%, and the mass of the defoaming agent accounts for 0.4-0.6wt.%.
9. A composite material component prepared by the method for integrated forming of a continuous ceramic gradient distribution reinforced composite material according to any one of claims 1 to 8, characterized in that: The composite material component uses aluminum alloy as the matrix and continuous porous ceramics with a density gradient change along a preset direction as the reinforcement phase. It is prepared through an extrusion casting, infiltration and integrated forming method to have gradient wear resistance, toughness and strength properties.
Citation Information
Patent Citations
Gradient porous ceramic preform, aluminum alloy toughened ceramic composite material and preparation
CN113773053A
Metal-based ceramic composite material and preparation method thereof
CN114226691A
Preparation method of porous ceramic local reinforced composite material automobile brake pad
CN114292126A
Preparation method of gradient aperture porous ceramic
CN118666574A
Method to produce ceramic reinforced or ceramic-metal matrix composite articles
US5167271A